2020
DOI: 10.1080/00343404.2020.1813881
|View full text |Cite
|
Sign up to set email alerts
|

The new normative: synergistic scenario planning for carbon-neutral cities and regions

Abstract: Carbon-neutral targets are a 'new normative' for cities and regions around the world. Such targets call for rapid system transformations, far beyond the previous scope of urban-regional planning. In response we propose a framework of theory and practice, in three parts: 'trading zone' concepts for collaborative planning; 'scenario backcasting' for longer horizons; and 'synergistic thinking' for systems transformation. We demonstrate this with the case study of Greater Manchester and its many phases of carbon-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…vision-crafting, in the course of history, the concept of the "ideal city" has influenced the Western world both as a regulative model and a source of inspiration (Rosenau, 2013). By the same token, in the "urban age," recent urban imaginaries originally developed in the Global Northaim at proposing an all-encompassing destination for the highly sought urban transformation (Khan and Zaman, 2018): resilient city (Jabareen, 2013), creative city (Landry, 2012), compact city (Burton et al, 2003), zero carbon city (Urrutia-Azcona et al, 2019;Ravetz et al, 2021), sharing city (Agyeman and McLaren, 2017), smart sustainable cities (Bibri, 2018), "Smart with a Heart" (Menny et al, 2018), Ecocity (Wong and Yuen, 2011), smart city 2.0 (Trencher, 2019), gender-equal cities (Sandberg and Ro ¨nnblom, 2016), age-friendly cities (Buffel et al, 2012), car-free cities (Inayatullah, 2011), etc. Nonetheless, recent scholarship in urban imaginaries has tried to problematize urbanism beyond the predominately gendered Western narrative and argue in favor of context-specific approaches to urban futures.…”
Section: Foresight and Urban Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…vision-crafting, in the course of history, the concept of the "ideal city" has influenced the Western world both as a regulative model and a source of inspiration (Rosenau, 2013). By the same token, in the "urban age," recent urban imaginaries originally developed in the Global Northaim at proposing an all-encompassing destination for the highly sought urban transformation (Khan and Zaman, 2018): resilient city (Jabareen, 2013), creative city (Landry, 2012), compact city (Burton et al, 2003), zero carbon city (Urrutia-Azcona et al, 2019;Ravetz et al, 2021), sharing city (Agyeman and McLaren, 2017), smart sustainable cities (Bibri, 2018), "Smart with a Heart" (Menny et al, 2018), Ecocity (Wong and Yuen, 2011), smart city 2.0 (Trencher, 2019), gender-equal cities (Sandberg and Ro ¨nnblom, 2016), age-friendly cities (Buffel et al, 2012), car-free cities (Inayatullah, 2011), etc. Nonetheless, recent scholarship in urban imaginaries has tried to problematize urbanism beyond the predominately gendered Western narrative and argue in favor of context-specific approaches to urban futures.…”
Section: Foresight and Urban Planningmentioning
confidence: 99%
“…Most case studies are multimethod, visionary and feature a city from the Global North. Also, the foresight nomenclature varies in the articles from synergy foresight (Ravetz and Miles, 2016; Ravetz et al , 2021), urban retrofitting (Dixon et al , 2014) and sustainability visioning (Iwaniec and Wiek, 2014), to participatory foresight (Kitagawa and Vidmar, 2022; Gudowsky et al , 2017), multi-layered foresight (Dufva et al , 2015) and city foresight (Dixon et al , 2022; Mahmud, 2011).…”
Section: Foresight and Urban Planningmentioning
confidence: 99%
“…These goals require rapid transformation outside the ordinary traditional urban regional planning. Through research into carbon neutrality in Greater Manchester, academics demonstrated that "collaborative scenario planning" dramatically contributes to "new norms" in cities and regions (Ravetz et al, 2020). Academic research showed that better urban and transport planning could result in carbon-neutral, healthy cities, mainly through land-use change, a shift from private motorised transport to public and active transport, and urban greening (Nieuwenhuijsen, 2020).…”
Section: Carbon Neutral Citymentioning
confidence: 99%
“…The transnational municipal 'ecosystem,' while primarily aspirational (Bansard et al 2017) The third-generation climate action planning process distils these ingredients into evidence-based pathways, which have been instrumental in securing political consensus and translating political will into work plans, bridging ambition, and operations, while acting as a rallying cry for engaged citizens (Ravetz et al 2021). The approval of the plans by councils reviewed in this paper has empowered staff to enlarge their efforts and ambition to more closely align with science-based targets.…”
Section: The Collective Impactmentioning
confidence: 99%